Pengaruh Jumlah Jam Belajar Terhadap Nilai Siswa Dengan Metode Regresi Linear Sederhana - Zaidan Nawfal (Jejaring Penelitian dan Pengabdian Masyarakat (JPPM), 2025)
This research aims to determine the effect of study hours on student grades. To increase student grades, there are influencing factors, one of which is the number of study hours. Obstacles that often occur to improving grades are students' lack of awareness about their lack of interest in learning and the small number of study hours spent outside of class. This research uses a simple linear regression method and uses orange data mining tools, the results show that there is a relationship between study hours and student grades. Data shows that the more time students spend studying, the better their academic scores. The final results of this research can provide important information to teachers, parents and students about the importance of allocating sufficient study time to achieve the best grades and can help us understand the factors that influence student learning and provide a basis for developing better learning strategies.